Active corrosion protection of various aluminium alloys by lithium‐leaching coatings. (7th March 2019) - Visser, Peter; Terryn, Herman; Mol, Johannes M.C.
Abstract : This study presents the active protective properties of lithium‐leaching coatings for a range of aluminium alloys. Coatings with and without lithium carbonate as leachable inhibitor were applied on the aluminium alloys, artificially damaged and exposed to the neutral salt spray. A combined approach of scanning electron microscopy and electrochemical measurements revealed that the lithium carbonate leaching coating provided effective corrosion inhibition on AA2024, AA7075, AA5083, and AA6014 by the formation of a protective layer in the defect area and preventing local corrosion processes despite the different intrinsic electrochemical activity of the alloys.